Evaluating Virtual Reality Simulations for Wheel Loader Inspection - Borges, Luiz Felipe Muniz Rocha; Viana, Pedro Henrique Porto; de Oliveira, Tainã Ribeiro; Martins, Thiago da Silva; Andreão, Rodrigo Varejão; Schimidt, Marcelo; Mestria, Mário (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2023: Anais do XXV Simpósio de Realidade Virtual e Aumentada, 2023)
In this study, a virtual reality simulation game for the inspection of a wheel loader is proposed. It has a cost-effective way to provide training and to monitor the performance of machinery operators in a mining company. This game is used during their mandatory pre-operation safety inspection, a tool that is otherwise nonexistent for their specific needs. The simulator was developed using a game engine and built to operate with different virtual reality headsets. It aims to use a guide to perform inspection procedures on a wheel loader of a mining company. A team of professional collaborators from the mining company evaluated the simulator under several scenarios. The computational results showed that the simulator provided the employees with an initial experience before conducting an actual field inspection of the wheel loader. In this sense, the simulator increases the safety of employees and does not expose them to risky situations, owing to a deeper knowledge of inspection procedures. Moreover, the simulator has a lower cost compared to an outsourced contract and can decrease machine downtime. Finally, the simulator is effective for training because it provides professional employees with a sense of realism.